Effects of Jinkui Shenqi and Wuzi Yanzong pill on sperm motility and sperm DNA fragmentation rate in asthenospermia (Bioscience Journal, 2022)
This study was designed to compare the effects of Jinkui Shenqi and Wuzi Yanzong pill on sperm motility and sperm DNA fragmentation rate in patients with asthenospermia. 130 cases were randomly divided into an observation and control group (n=65). The control group was treated with the Wuzi Yanzong pill while the observation group with the Jinkui Shenqi pill. The sperm motility parameters rate (PR), semen concentration, sperm motility, DFI and α-glucosidase, fructose, seminal plasma zinc (Zn), acid phosphatase (ACP) in seminal plasma biochemistry and other indexes of were observed. The biochemical indexes of seminal plasma of α-glucosidase, fructose, Zn, ACP in two groups were significantly (p